Gender Differences in Information and Communication Technology Competencies among Librarians in Indonesia - Rahmi, Rahmi; Kamil, Rusdan; Fitriani, Dian Novita (BACA: Jurnal Dokumentasi dan Informasi, 2023)
ABSTRACTThis study evaluates the Information and Communication Technology (ICT) competency frameworks for librarians in Indonesia, focusing on gender differences. Despite the critical role of these frameworks in addressing digital age challenges, their efficacy in capturing gender-specific nuances in competencies is underexplored. This research surveyed 208 librarians, employing a questionnaire derived from the 2019 Indonesian National Qualifications Framework for Libraries (SKKNI). The survey, distributed via Google Forms, targeted librarians in various library types across Indonesia. Employing accidental random sampling, this research revealed significant disparities in ICT-related competencies across genders. While gender did not majorly influence the demographic characteristics of librarians in the ICT division, notable differences emerged in ICT competency based on gender. These findings highlight the need for gender-sensitive approaches in developing ICT competencies and suggest revisions to current frameworks to address gender-specific needs better, contributing to a deeper understanding of digital literacy and equity in Indonesian librarianship. ABSTRAK Penelitian ini mengevaluasi kerangka kompetensi Teknologi Informasi dan Komunikasi (TIK) untuk pustakawan di Indonesia dengan fokus pada perbedaan gender. Meskipun kerangka ini penting dalam menghadapi tantangan era digital, efektivitasnya dalam menangkap nuansa spesifik gender dalam kompetensi belum banyak diteliti. Peneliti melakukan survei terhadap 208 pustakawan dengan menggunakan kuesioner yang berasal dari Standar Kompetensi Kerja Nasional Indonesia (SKKNI) 2019 untuk Perpustakaan. Survei ini, yang disebar melalui Google Forms, menargetkan pustakawan dari berbagai jenis perpustakaan di Indonesia. Menggunakan sampling acak, penelitian ini mengungkapkan perbedaan yang signifikan dalam kompetensi TIK berdasarkan gender. Meskipun gender tidak terlalu mempengaruhi karakteristik demografis pustakawan di divisi TIK, perbedaan yang mencolok muncul dalam kompetensi TIK berdasarkan gender. Temuan ini menyoroti perlunya pendekatan sensitif gender dalam mengembangkan kompetensi TIK dan menyarankan revisi pada kerangka kerja saat ini untuk lebih mengakomodasi kebutuhan spesifik gender, berkontribusi pada pemahaman yang lebih dalam tentang literasi digital dan kesetaraan dalam kepustakawanan di Indonesia